Identifikasi Karakter Petani dan Peran Penyuluh Pada Kelompok Tani Padi di Desa Siaro - Sihombing, Shelly M.; Abdina, Muhammad Fadly (Jurnal Ilmiah Pertanian ( JIPERTA), 2025)
This research aims to determine the identification of farmer characteristics and the role of agricultural instructors in lowland rice farmer groups (Case Study: Siaro Village, Siborongborong District, North Tapanuli Regency). The data analysis method for this research is descriptive qualitative, with the research object being 37 farmers from the lowland rice farming group. Primary data was obtained through a questionnaire that identified the characteristics of farmers and the role of extension workers, as well as interviews with respondents using a prepared questionnaire. The research results show that the majority of lowland rice farmers in Siaro Village are men (59.5%), and most have a high school education level (73%). In terms of farming experience, the majority of respondents had 21-30 years of experience (29.7%). The role of agricultural instructors in rice farming groups in this village has proven to be significant, with instructors functioning as educators, facilitators, communicators, innovators and motivators. According to the data, 67.6% of farmers feel that extension workers play an important role in their farming business, according to an interval scale of 75-104.